Investigation on corrosion and tensile Characteristics: Friction stir welding of AA7075 and AA2014. (2022) - Haribalaji, V.; Venkatesan, G.; Asif.M, Mohammed; Pandian, Mani; Subbiah, Ram; Boopathi, S.
Abstract: In this article, the corrosion and tensile strength characteristics of Friction-stir-Welding(FSW) of AA7075 and AA2014 have been investigated. These Aluminium alloy materials have widely been used in making automotive, aerospace, and nautical industrial components. The nine specimens have been made by tool rotational speed and welding speed using full factorial design. The optimum tool rotational speed and welding speed were predicted using statistical analysis for both maximum tensile strength and minimum corrosion rate. The minimum corrosion rate (805.3 miles/year) was obtained from maximum speed of tool rotation (1400 rpm) and welding speed (60 mm/min); maximum tensile strength (194. 6 MPa) has been attained by moderate tool rotational speed (1200 rpm) and welding speed (45 mm/min). The specimens for the tensile and corrosion tests were prepared with optimum settings. The microstructure of corroded surface had been illustrated using scanning electron microscopy (SEM) images.